Longitudinal β-Amyloid Deposition and Hippocampal Volume in Preclinical Alzheimer Disease and Suspected Non–Alzheimer Disease Pathophysiology - Gordon, Brian A. (JAMA Neurol, 2016)
IMPORTANCE: Preclinical Alzheimer disease (AD) can be staged using a 2-factor model denoting the presence or absence of β-amyloid (Aβ+/−) and neurodegeneration (ND+/−). The association of these stages with longitudinal biomarker outcomes is unknown. OBJECTIVE: To examine whether longitudinal Aβ accumulation and hippocampal atrophy differ based on initial preclinical staging. DESIGN, SETTING, AND PARTICIPANTS: This longitudinal population-based cohort study used data collected at the Knight Alzheimer Disease Research Center, Washington University, St Louis, Missouri, from December 1, 2006, to June 31, 2015. Cognitively normal older adults (n = 174) were recruited from the longitudinal Adult Children Study and Healthy Aging and Senile Dementia Study at the Knight Alzheimer Disease Research Center. At baseline, all participants had magnetic resonance imaging (MRI) scans, positron emission tomography (PET) scans with carbon 11-labeled Pittsburgh Compound B (PiB), and cerebrospinal fluid assays of tau and phosphorylated tau (ptau) acquired within 12 months. Using the baseline biomarkers, individuals were classified into preclinical stage 0 (Aβ−/ND−), 1 (Aβ+/ND−), or 2+ (Aβ+/ND+) or suspected non-AD pathophysiology (SNAP; Aβ−/ND+). MAIN OUTCOMES AND MEASURES: Subsequent longitudinal accumulation of Aβ assessed with PiB PET and loss of hippocampal volume assessed with MRI in each group. RESULTS: Among the 174 participants (81 men [46.6%]; 93 women [53.4%]; mean [SD] age, 65.7 [8.9] years), a proportion (14%-17%) of individuals with neurodegeneration alone (SNAP) later demonstrated Aβ+. The rates of Aβ accumulation and loss of hippocampal volume in individuals with SNAP were indistinguishable from those without any pathologic features at baseline (for Aβ accumulation: when hippocampal volume was used to define ND, t = 0.00 [P > .99]; when tau and ptau were used to define ND, t = −0.02 [P = .98]; for loss of hippocampal volume: when hippocampal volume was used to define ND, t = −1.34 [P = .18]; when tau and ptau were used to define ND, t = 0.84 [P = .40]). Later preclinical stages (stages 1 and 2+) had elevated Aβ accumulation. Using hippocampal volume to define ND, individuals with stage 1 had accelerated Aβ accumulation relative to stage 0 (t = 11.06; P < .001), stage 2+ (t = 2.10; P = .04), and SNAP (t = 9.32; P < .001), and those with stage 2+ had accelerated Aβ accumulation relative to stage 0 (t = 4.38; P < .001) and SNAP (t = 4.08; P < .001). When ND was defined using tau and ptau, individuals with stage 2+had accelerated Aβ accumulation relative to stage 0 (t = 4.96) and SNAP (t = 4.06), and those with stage 1 had accelerated Aβ accumulation relative to stage 0 (t = 8.44) and SNAP (t = 6.61) (P < .001 for all comparisons). When ND was defined using cerebrospinal fluid biomarkers, individuals with stage 2+ had accelerated hippocampal atrophy relative to stage 0 (t = −3.41; P < .001), stage 1 (t = −2.48; P = .03), and SNAP (t = −2.26; P = .03). CONCLUSIONS AND RELEVANCE: More advanced preclinical stages of AD have greater longitudinal Aβ accumulation. SNAP appears most likely to capture inherent individual variability in brain structure or to represent comorbid pathologic features rather than early emerging AD. Low hippocampal volumes or elevated levels of tau or ptau in isolation may not accurately represent ongoing neurodegenerative processes.